WAYS OF IMPROVING STUDENTS’ COMMUNICATIVE SKILLS IN TEACHING ENGLISH - Rayhona Abdukhalilova (Web of Journals Publishing, 2025)
This article effective communication skills are crucial for language learners as they form the foundation of successful language acquisition. This article explores various strategies to improve students' communicative competence in English language teaching. Key methods include interactive activities, task-based learning, role-playing, peer collaboration, and multimedia tools. The paper emphasizes the importance of creating a supportive learning environment to foster confidence and active participation among students.
Keywords: Communicative skills, English language teaching, task-based learning, role-playing, multimedia tools, peer collaboration, interactive activities, language acquisition.